2020
DOI: 10.1142/s0217979220500289
|View full text |Cite
|
Sign up to set email alerts
|

Computation of electroconductive gyrotactic bioconvection under nonuniform magnetic field: Simulation of smart bio-nanopolymer coatings for solar energy

Abstract: The water-based bioconvection of a nanofluid containing motile gyrotactic micro-organisms (moves under the effects of gravity) over a nonlinear inclined stretching sheet in the presence of a nonuniform magnetic field has been investigated. This regime is encountered in the bio-nanomaterial electroconductive polymeric processing systems currently being considered for third-generation organic solar coatings, anti-fouling marine coatings, etc. Oberbeck–Boussinesq approximation along with ohmic dissipation (Joule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…The mechanism of bioconvection can be exploited in producing ecological fuels, bio-coatings and designing fuel systems. Relevant studies include Chisti [15] on bioethanol, Satyanarayana et al [16] on PEM fuel cells [16], Aneja et al [17] on magnetic nano-bio solar collector coatings and Roncallo et al [18] on photo-bioreactors. Many numerical studies of combined nanofluid and bioconvection transport have been reported recently.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of bioconvection can be exploited in producing ecological fuels, bio-coatings and designing fuel systems. Relevant studies include Chisti [15] on bioethanol, Satyanarayana et al [16] on PEM fuel cells [16], Aneja et al [17] on magnetic nano-bio solar collector coatings and Roncallo et al [18] on photo-bioreactors. Many numerical studies of combined nanofluid and bioconvection transport have been reported recently.…”
Section: Introductionmentioning
confidence: 99%
“…An excellent discussion on bioconvection patterns can be seen in the literature 12–14 . Bioconvection within nanofluids comprises the most gifted nanoplatform because such bioconvective nanoliquid flow has wide applications in the bio‐micro‐system, 15 bioreactors, 16 biochromatography, 17 magnetic bioseparation devices, 18 biosensors, 19 biocoating, 20 ecological fuels, 21 biochemical reactors, 22 and so forth. Geng and Kuznetsov 23 investigated the impression of minuscule particles on bioconvection.…”
Section: Introductionmentioning
confidence: 99%
“…Andersson et al [17] analyzed studied hydromagnetic power-law fluid over a stretching sheet, deriving exact similarity transformation, although they incorrectly computed flow acceleration with stronger magnetic field effect. Aneja and co-workers [18] employed the variational finite element method to compute the gyrotactic bioconvection in power-law magnetic flow from a tilted stretching sheet. They computed the correct response of increasing magnetic field, namely that it reduces momentum boundary layer thickness and decelerates the flow.…”
Section: Introductionmentioning
confidence: 99%